Long-term trends and future projections of the burden of tuberculosis among children and adolescents in China - Nan Li; Wei Wei; Yinglin Lao; Xi Zhu; Qi Ye; Junhong Chen; Yating Ji; Ruoqing Chen; Chongguang Yang (PLoS ONE, 2025)
Background China ranks third in estimated TB incidence in 2023, accounting for 6.8% of the global cases. TB in children and adolescents is a public health issue that today warrants priority attention in China. Objective The purpose of this study was to investigate the burden of TB among Chinese children and adolescents aged 0–19 years from 1990 to 2021 and to estimate the incidence rate, mortality rate, and disability-adjusted life years (DALYs) rate from 2022 to 2031. Methods The Joinpoint regression analysis was used to identify periods of significant change and autoregressive Integrated Moving Average (ARIMA) modeling was employed to predict the TB burden for 2022–2031. Results The study indicated that China has significantly reduced the TB burden among children and adolescents over the past 32 years, the most pronounced reductions in incidence occurred during the periods 2010–2015 (APC = −8.64%, P < 0.05) and 2019–2021 (APC = −6.09%, P < 0.05). Meanwhile, death and DALYs rates showed a consistently rapid decline across the entire 32-year span. Adolescents aged 15–19 years have the highest incidence rates, and children under 5 continue to face high mortality and DALYs rates. Additionally, females experienced a more significant decline compared to males across all age groups. Despite minor fluctuations in some age groups, a downward trend in incidence, death, and DALYs rates was anticipated to continue until 2031, with persistent gender differences in future projections. Conclusions Our findings demonstrate a persistent downward trajectory in TB burden among Chinese children and adolescents from 1990 to 2021, with significant gender disparities favoring females across all age groups. Notably, children younger than 5 years and adolescents aged 15–19 years are at higher risk, which emphasizes the importance of tailored interventions to ensure continued progress towards comprehensive TB control goals.